Flow-mediated growth of an aquatic herbivore - Chris Hansen; Sue Newman; Colin J. Saunders; Erik K. Tate-Boldt; Nathan J. Dorn (Hydrobiologia, 2022)

Aging and white matter microstructure and macrostructure: a longitudinal multi-site diffusion MRI study of 1218 participants - Kurt G. Schilling; Derek Archer; Fang-Cheng Yeh; Francois Rheault; Leon Y. Cai; Colin Hansen; Qi Yang; Karthik Ramdass; Andrea T. Shafer; Susan M. Resnick; Kimberly R. Pechman; Katherine A. Gifford; et al. (Brain Structure and Function, 2022)

A comment on: magma residence and eruption at the Taupō Volcanic Center (Taupō Volcanic Zone, New Zealand)—insights from rhyolite-MELTS geobarometry, diffusion chronometry, and crystal textures, by AS Pamukçu et al., Contrib Mineral Petrol 175:48 (2020) - Colin J. N. Wilson; Simon J. Barker; Bruce L. A. Charlier; Madison L. Myers; Kristian F. Hansen (Contributions to Mineralogy and Petrology, 2021)

A new approach for estimating and delineating within-field crop water stress zones with satellite imagery - Ryan Smith; Lindi Oyler; Colin Campbell; Elisa A. Woolley; Bryan G. Hopkins; Ruth Kerry; Neil C. Hansen (International Journal of Remote Sensing, 2021)

Pandora: 4-D White Matter Bundle Population-Based Atlases Derived from Diffusion MRI Fiber Tractography - Colin B Hansen; Qi Yang; Ilwoo Lyu; Francois Rheault; Cailey Kerley; Bramsh Qamar Chandio; Shreyas Fadnavis; Owen Williams; Andrea T. Shafer; Susan M. Resnick; David H. Zald; Laurie E Cutting; et al. (Neuroinformatics, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

A natural product biflavonoid scaffold with anti-tryptase activity - Nicholas F. Fazio; Michael H. Russell; Steven M. Flinders; Colin J. Gardner; Jace B. Webster; Marc D.H. Hansen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Correction to: Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Disinfection and removal of human pathogenic bacteria in arctic waste stabilization ponds - Yannan Huang; Lisbeth Truelstrup Hansen; Colin M. Ragush; Rob C. Jamieson (Environmental Science and Pollution Research, 2018)

Drought timing and local climate determine the sensitivity of eastern temperate forests to drought - Loïc D'Orangeville; Justin Maxwell; Daniel Kneeshaw; Neil Pederson; Louis Duchesne; Travis Logan; Daniel Houle; Dominique Arseneault; Colin M. Beier; Daniel A. Bishop; Daniel Druckenbrod; Shawn Fraver; et al. (Global Change Biology, 2018)
Projected changes in temperature and drought regime are likely to reduce carbon (C) storage in forests, thereby amplifying rates of climate change. While such reductions are often presumed to be greatest in semi‐arid forests that experience widespread tree mortality, the consequences of drought may also be important in temperate mesic forests of Eastern North America ( ENA ) if tree growth is significantly curtailed by drought. Investigations of the environmental conditions that determine drought sensitivity are critically needed to accurately predict ecosystem feedbacks to climate change. We matched site factors with the growth responses to drought of 10,753 trees across mesic forests of ENA , representing 24 species and 346 stands, to determine the broad‐scale drivers of drought sensitivity for the dominant trees in ENA . Here we show that two factors—the timing of drought, and the atmospheric demand for water (i.e., local potential evapotranspiration; PET )—are stronger drivers of drought sensitivity than soil and stand characteristics. Drought‐induced reductions in tree growth were greatest when the droughts occurred during early‐season peaks in radial growth, especially for trees growing in the warmest, driest regions (i.e., highest PET ). Further, mean species trait values (rooting depth and ψ 50 ) were poor predictors of drought sensitivity, as intraspecific variation in sensitivity was equal to or greater than interspecific variation in 17 of 24 species. From a general circulation model ensemble, we find that future increases in early‐season PET may exacerbate these effects, and potentially offset gains in C uptake and storage in ENA owing to other global change factors.

The 5-HT2C receptor agonist meta-chlorophenylpiperazine (mCPP) reduces palatable food consumption and BOLD fMRI responses to food images in healthy female volunteers - Jason M. Thomas; Colin T. Dourish; Jeremy Tomlinson; Zaki Hassan-Smith; Peter C. Hansen; Suzanne Higgs (Psychopharmacology, 2018)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Oceanographic regime shift during 1997 in Disko Bay, Western Greenland - Marc Overgaard Hansen; Torkel Gissel Nielsen; Colin A. Stedmon; Peter Munk (Limnology and Oceanography, 2012)
Data from a long time series of temperature, salinity, and nutrient measurements in Disko Bay (West Greenland) reveal a marked change in the water characteristics during recent years. Seasonal dynamics in the upper 150 m of the water column were highly affected by the seasonality in meteorological conditions, while the deeper water strata were more stable and were primarily influenced by large‐scale circulation patterns. There was a marked increase in the average water temperatures at 200‐m depth in spring 1997, with the long‐term average increasing from 1.30°C to 2.25°C. Weekly data from 1996 to 1997 show that the sudden change in bottom water occurred in April 1997, due to the inflow of a larger proportion of North Atlantic water, which propagated north along the coast before entering the bay. Further support for this inflow was found when tracing the relative proportion of Atlantic water in the bay, using inorganic nutrients. These changes in the oceanography of the bay will not only lead to further glacial retreat but will also affect the local marine ecosystem by changing the relative dominance of major copepod species that overwinter in bottom waters of the bay.

Rapid Assessment of the Nutritional Value of Foods Eaten by Mountain Gorillas: Applying Near-Infrared Reflectance Spectroscopy to Primatology - Jessica M. Rothman; Colin A. Chapman; Julie L. Hansen; Debbie J. R. Cherney; Alice N. Pell (International Journal of Primatology, 2009)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)